Can emergency physicians 'rule in' and 'rule out' acute myocardial infarction with clinical judgement?. Issue 11 (12th July 2014) - Body, Richard; Cook, Gary; Burrows, Gillian; Carley, Simon; Lewis, Philip S
Abstract : Objective: To determine the diagnostic accuracy of emergency physician gestalt in emergency department (ED) patients with suspected cardiac chest pain, both alone and in combination with initial troponin level and ECG findings. Methods: We prospectively included patients presenting to the ED with suspected cardiac chest pain. Clinicians recorded their 'gestalt' at the time of presentation using a five-point Likert scale, blinded to outcome. Troponin T and high-sensitivity troponin T (hs-cTnT; both Roche Diagnostics Elecsys) levels were measured in admission blood samples. All patients underwent troponin testing at least 12 h after peak symptoms. The primary outcome was acute myocardial infarction (AMI). Results: 458 patients were included in this study, 81 (17.7%) of whom had AMI. Clinician gestalt alone had an area under the receiver operating characteristic curve of 0.76 (95% CI 0.70 to 0.82) for AMI. Immediately discharging patients with normal initial troponin and ECG in whom the clinician felt the diagnosis was 'probably not' or 'definitely not' acute coronary syndrome (ACS) would have avoided admission for 23.1% (95% CI 19% to 28%) patients with 100% sensitivity (95% CI 95.6% to 100%). With hs-cTnT, 100% sensitivity could have been achieved even if only patients with 'probable' or 'definite' ACS were investigated further, which would have allowed 41.7% patients to be discharged immediately. Conclusions: Gestalt alone cannot be used to 'rule in' or 'rule out' ACS. By combining clinician gestalt with the admission ECG and troponin level, we found 100% sensitivity without the need for serial troponin testing. These findings have the potential to reduce unnecessary hospital admissions for suspected ACS but must be prospectively validated before considering clinical implementation.